Cross type defected ground structure integrated microstrip antenna: a novel perspective for broad banding and augmenting polarization purity. Issue 5 (24th March 2017) - Ghosh, Abhijyoti; Chattopadhyay, Sudipta; Chakraborty, Subhradeep; Basu, Banani
Abstract: A simple cross type defected ground structure (CDGS) integrated rectangular microstrip antenna (RMA) has been proposed to achieve broad bandwidth along with augmented (improved) co-polarized to cross-polarized radiation (CP-XP) isolation over principal and diagonal planes. In this design, a crucial emphasis is given for concurrent improvement of both bandwidth and polarization purity of microstrip antenna without hampering dominant mode fields. Around 25–28 dB CP-XP isolation is achieved over wide elevation angle with the proposed structure with 25% impedance bandwidth. The simulated and measured results show a close resemblance with each other. The proposed geometry is very simple, easy to fabricate and therefore helps in effortlessness manufacturing process. Therefore, the present structure appears to be ideal in numerous applications where polarization purity is the key issue over the wide bandwidth.